Analysis of the potential dimensions and influencing factors of nurses’ sense of professional achievement in “Internet + Nursing Services” - Wu, Jing; Zhang, Zhixia; Li, Juanjuan; Li, Heng; Zhang, Niannian; Gao, Lili; He, Congcong; Wang, Xuan (Frontiers in Public Health, 2025)
BackgroundWith the current development of smart technology and information in society, the integration of “Internet+” and medical services provides new solutions to tackle the current shortage of nursing resources. The feeling of professional success plays an important role in keeping the nursing workforce stable and improving the quality of nursing services. This study looks at "Internet + Nursing Services" and aims to explore the different types of professional success for nurses in this field. It also analyzes the key factors that shape each type in depth, providing a solid research foundation to improve the work environment for nurses and enhance the attractiveness.MethodsA convenience sampling method was used to select 378 nurses providing “Internet + Nursing Services” from six top-tier hospitals across different regions of Shanxi Province (two hospitals each from Jinbei, Jinzhong, and Jinnan) between August and October 2024. A questionnaire survey was conducted using general information forms, the Nurse Career Success Scale, the Psychological Capital Scale, the Work-Family Support Scale, the Perceived Social Support Scale, and the Nursing Work Environment Scale. We conducted a latent profile analysis to examine the career success of nurses providing “Internet + Nursing Services,” and variance analysis and multi-class logistic regression analysis were performed to analyze the factors influencing career success among these nurses.ResultsThe career success of the nurses providing “Internet + Nursing Services” was divided into three latent profiles: a low career success group (51 nurses, 13.5%), a medium career success group (201 nurses, 53.2%), and a high career success group (126 nurses, 33.3%). The analysis showed that marital status, per capita annual family income, work-family support, and psychological capital are the influencing factors of career success among the nurses providing “Internet + Nursing Services.”ConclusionThe career success of nurses providing “Internet + Nursing Services” showed significant differences across categories. We should develop targeted interventions based on the different characteristics and factors affecting each group to enhance the career success of these nurses.